SU(3)c⊗SU(4)L⊗U(1)X model for three families (2004)
ABSTRACT: An extension of the Standard Model to the local gauge group SU(3)c⊗SU(4)L⊗U(1)XSU(3)c⊗SU(4)L⊗U(1)X as a three-family model is presented. The model does not contain exotic electric charges and we obtain a consistent mass spectrum by introducing an anomaly-free discrete Z2Z2 symmetry. The neutral currents coupled to all neutral vector bosons in the model are studied. By using experimental results from the CERN LEP, SLAC Linear Collider and atomic parity violation we constrain the mixing angle between two of the neutral currents in the model and the mass of the additional neutral gauge bosons to be −0.0032≤sinθ≤0.0031−0.0032≤sin⁡θ≤0.0031 and 0.67TeV≤MZ2≤6.10.67TeV≤MZ2≤6.1 TeV at 95% C.L., respectively.